Non-p.V600E BRAF Mutations Are Common Using a More Sensitive and Broad Detection Tool. Issue 4 (1st October 2015) - Carter, Jamal; Tseng, Li-Hui; Zheng, Gang; Dudley, Jonathan; Illei, Peter; Gocke, Christopher D.; Eshleman, James R.; Lin, Ming-Tseh
Abstract: Objectives: To assess the performance of a next-generation sequencing (NGS) platform for the clinical detection of BRAF mutations. Methods: In this retrospective quality assessment of an NGS assay, we analyzed BRAF mutations within parts of exons 11 and 15 in 835 neoplastic tissues submitted to our molecular diagnostics laboratory. Results: The NGS assays detected a BRAF mutation in 5.9% of lung adenocarcinomas, 13% of colorectal cancers, and 44% of melanomas. Mutant allele frequencies were less than 20% in 28% of 88 BRAF -mutated specimens. Two lymph node specimens with subcapsular or infiltrative metastasis showed 1% to 2% mutant alleles. There were 26 unique BRAF mutations in exons 11 and 15, including three novel mutations. Mutations were located outside codon 600 in 39% of BRAF -mutated tumors. Lung adenocarcinomas showed significantly higher non-p.V600E mutations (86%) than did colorectal cancers (23%) and melanomas (34%). The three most common BRAF mutations in lung cancers accounted for only 41% of the observed BRAF mutations (p.D594G [18%], p.V600E [14%], and p.G469A [9%]). Conclusions: The NGS assay demonstrated a high analytic sensitivity and a broad reportable range for clinical detection of BRAF mutations. Elucidating the spectrum of non-p. V600E BRAF mutations in different malignancies is a first step toward understanding their clinical significance.